Carbon emission transfer strategies in supply chain with lag time of emission reduction technologies and low-carbon preference of consumers. (10th August 2020) - Sun, Licheng; Cao, Xiaoxiao; Alharthi, Majed; Zhang, Jijian; Taghizadeh-Hesary, Farhad; Mohsin, Muhammad
Abstract: The construction of a low-carbon supply chain is central for the sustainable development of a country, especially for a large carbon emitter such as China. To better promote supply chain emission reduction, this paper analyzes the carbon emission transfer and emission reduction problem among enterprises within the supply chain, integrating the influence of government emission reduction policies and the low carbon market. Considering the lag time of emission reduction technologies and the low-carbon preferences of consumers, a Stackelberg differential game model (dominated by manufacturers) is constructed under both centralized and decentralized decisions. The results suggest that the lag time of emission reduction technology and the low carbon preference of consumers positively affect the carbon emission transfer level of manufacturers, while not affecting suppliers' undertaking levels. Only when the lag time of emission reduction technology remains within a specific range, will an increase in consumers' low-carbon preferences exert a positive impact on supply chain profits. Notably, under decentralized decision-making, when the emission reduction technology lag time and consumers' low carbon preference remain within a specific range, the carbon emission transfer behavior exerts a positive promoting effect on the emission reduction of the supply chain. This applies when the profit of the supply chain increases and the carbon emission reduction per unit of product decreases. This result provides a new idea for the government to control irrational carbon emission transfer behavior of enterprises. Moreover, considering the lag time of emission reduction technology is also conducive to increasing the acceptability of government carbon quota.